2012
DOI: 10.1007/s11136-012-0268-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of proximal outcomes of self-management programs: translation and psychometric evaluation of a German version of the Health Education Impact Questionnaire (heiQ™)

Abstract: The German heiQ™ is comprehensible for German-speaking patients suffering from different types of chronic conditions; it assesses relevant outcomes of self-management programs in a reliable and valid manner. Further studies involving its practical application are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
71
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 54 publications
(62 reference statements)
16
71
1
2
Order By: Relevance
“…The final instrument has eight scales, which have been translated and culturally adapted into over 20 languages, and are currently being applied in clinical trials worldwide, including in Norway [12][13][14][15]. However, only a few studies have reported the psychometric performance of the heiQ in the diverse settings, in which it is being applied [16][17][18][19][20][21][22]. The present study describes the psychometric properties of the Norwegian translation of the heiQ version 2.0 in diverse patient populations.…”
Section: Making Robust Decisions About the Impact Of Health Educationmentioning
confidence: 97%
See 2 more Smart Citations
“…The final instrument has eight scales, which have been translated and culturally adapted into over 20 languages, and are currently being applied in clinical trials worldwide, including in Norway [12][13][14][15]. However, only a few studies have reported the psychometric performance of the heiQ in the diverse settings, in which it is being applied [16][17][18][19][20][21][22]. The present study describes the psychometric properties of the Norwegian translation of the heiQ version 2.0 in diverse patient populations.…”
Section: Making Robust Decisions About the Impact Of Health Educationmentioning
confidence: 97%
“…Some of the final eight heiQ scales have been well-defined in the literature before, particularly Psychological distress, which has been shown to be strongly associated with similar well established scales relevant to heiQ [17]. However, other heiQ scales are unique constructs, making traditional concurrent validity studies difficult to undertake.…”
Section: Making Robust Decisions About the Impact Of Health Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Health Education Impact Questionnaire (heiQ) [24,25] was applied to evaluate immediate (proximal) outcomes of patient education. Three of its 8 scales were used: (a) Positive and active engagement in life (5 items; e.g., "I try to make the most of my life"); (b) Skill and technique acquisition (4 items; e.g., "I have effective ways of preventing symptoms"); and (c) Constructive attitudes and approaches (5 items; e.g., "I try not to let my health problems stop me from enjoying life").…”
Section: Assessmentsmentioning
confidence: 99%
“…Isso se deve, Cientes das limitações registradas na literatura para esse tipo de adaptação, introduzimos mudanças metodológicas semelhantes a achados recentes, dando maior peso à atuação do comitê de juízes no processo e favorecendo sua configuração interdisciplinar e sua participação por meio eletrônico. 1,[14][15][16][17][18] Um ponto a enfatizar é que não existe consenso em relação ao melhor método a ser empregado para formar o comitê de juízes. Cada estudo apresentou um formato de acordo com os critérios de inclusão que considerou adequado, percebido tanto em pesquisas que explicam a metodologia para se realizar tradução e adaptação, quanto naquelas que traduziram e adaptaram instrumentos.…”
unclassified